2012
DOI: 10.1109/tia.2012.2225813
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for Nonintrusive In Situ Efficiency Estimation of Induction Machines Operating With Unbalanced Supply Conditions

Abstract: The development of an in situ efficiency estimation technique is a challenging task where the lowest level of intrusion and the highest possible accuracy are required. In this paper, a new algorithm is discussed for the in situ efficiency estimation of induction machines under unbalanced power supplies. Prior work in the literature has concentrated on balanced supplies. In addition, to have a nonintrusive speed measurement, a specific adaptive nonlinear algorithm is applied for the extraction of the speed-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Given that [12] reported that accurate speed estimates implementing vibration analysis can be ascertained in 3 seconds (as opposed to [11] requiring 60 seconds), it is suggested that any real-time implementation of the NIEE-PBIL utilizes vibration analysis. This is due to the nature of the test requirements requiring measuring a machine's power profile at a singular thermal load point.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that [12] reported that accurate speed estimates implementing vibration analysis can be ascertained in 3 seconds (as opposed to [11] requiring 60 seconds), it is suggested that any real-time implementation of the NIEE-PBIL utilizes vibration analysis. This is due to the nature of the test requirements requiring measuring a machine's power profile at a singular thermal load point.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative implementation of determining speed from a motor's current signature is proposed in [11], where speed dependent harmonics that can be found in the stator current which are related to the supply frequency are extracted using a non-linear adaptive algorithm. The aforementioned method is able to estimate a machine's speed to within 0.07% of the measured speed [11].…”
Section: Non-intrusive Speed Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…To develop the software sensor, we propose a non-linear algorithm to obtain the frequency information. The technique used was introduced in [17,18]. It is mainly used for signals encountered on electrical domain.…”
Section: Real Time To Extract Informationmentioning
confidence: 99%